Teacher Communication Strategy in SMA Swasta Pencawan Medan - Helmida Barus; Dorsita Sitohang; Meyna Malango; Seprosari Simbolon (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to discuss teacher communication strategies to students in improving student achievement. According to researchers obstacles what teachers face in improving student achievement is concerned free time or opportunity to gather (discuss) between the teacher and student. This research is a type of qualitative research, which researchers as the key instrument, from the interview results the researcher gave a picture of that teacher communication strategies in creasing student achievement in more schools to rewards, in reality teacher often misinterterpret strategies this, The teacher only understands the form of punishment given to students who guilty, even thought the reward should also be given to students who achievers in the form of gifts, praise and others. From the three studies above it can be concluded In the learning process still found 15 students from 30 students who have difficulty in communicating, so it is very influential in the participation and achievement of students learning. To solve the problem, it is by using a learning method that requires students to be actively communicating, dare to express opinions. The problem that is examined in this research is how the form of teacher communication with the students occurs Keywords : communication strategies, English language learning.